Circuit provides hiccup-current limiting - How, C. H.; Basu, K. P. (UBM Tech, 2003)
Current-limit protection is an essential feature for power-supply systems. The three major types of current-limit-protection mechanisms are constant, foldback, and hiccup. Hiccup current limit performs the best of the three types; however, the implementation is rather complex. In this scheme, upon detection of an overcurrent event, the whole power supply shuts down for an interval before it tries to power itself up again. The cycle repeats until the overcurrent fault disappears. With such operation, the dissipation in the power supply itself is minimal. You can incorporate the circuit in.